Efektivitas Beberapa Fungisida Sintetis Terhadap Pertumbuhan Patogen Penyakit Kudis (Diaporthe phaseolorum C.&E.) pada Tanaman Jeruk Siam (Citrus nobilis L.) - NATHA, I PUTU MAHA DARMA; SUDANA, I MADE; SINGARSA, I DEWA PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.3, Juli 2022, 2022)
Effectiveness of Some Synthetic Fungicides to Scabies Disease Pathogen ( Diaporthe phaseolorum  C.&E.) Growth on Siam Orange Fruit ( Citrus nobilis  L.) Siam orange is one of the main commodities produced in Payangan District, Gianyar, Bali. Unfortunately, the Siam orange is often attacked by scabies. This disease is named scabies because it produces scab-like lesions that develop mainly on the skin of the fruit. Scabies is caused by the fungus  Diaporthe phaseolorum . In order to increase the production of Siam oranges in Payangan, it is necessary to control this pathogen. The purpose of this study was to determine the effectiveness of synthetic fungicides in controlling scabies in Siam orange fruit and to determine the most effective synthetic fungicides to use. This research was conducted in a citrus orchard in Kerta Village, Payangan District, Gianyar, Bali. PS3 treatment Mankozeb + Mefenoxam, was the most effective in suppressing the growth of scabies in Siam oranges. The average PS3 is the smallest in the percentage of disease per tree, which is 70%, followed by the average fruit diameter of PS3 which produces the largest fruit, which is 19.25 cm, as well as the average intensity of PS3 disease is the smallest, which is 24.63%. The results of observations carried out showed that the administration of synthetic fungicides was effective in suppressing the growth of pathogens that cause scabies in Siam oranges in Payangan, especially the synthetic fungicide Mankozeb + Mefenoxam.